PC.11 Neonatal outcomes of late and moderately preterm infants following spontaneous and no-spontaneous onset of labour. (9th June 2014) - Boyle, EM; Johnson, S; Draper, ES; Manktelow, B; Seaton, S; Evans, TA; Smith, LK; Marlow, N; Field, DJ
Abstract : Background: Infants born late/moderately preterm (LMPT; 32–36 weeks' gestation) have increased risk of adverse outcomes compared with term-born infants. It is unclear whether differences relate to prematurity per se, or to problems occurring during pregnancy leading to medically indicated delivery. Aim: To explore outcomes in LMPT and term infants born following spontaneous onset of labour (SOL) and non-spontaneous onset of labour (NSOL). Methods: In a prospective, population-based study, we compared neonatal outcomes of LMPT normally formed singleton infants according to whether birth followed SOL or NSOL. Outcomes included resuscitation at delivery, respiratory support, fluid and nutritional support. Results: 907 LMPT and 972 term-born infants were studied. NSOL occurred in 42.1% of LMPT and 34.2% of term births. Of these, 50.5% of LMPT and 31.9% of term infants were delivered by caesarean section not preceded by labour. The median (range) gestation was 35 +6 (32 +0, 36 +5 ) weeks for both preterm groups and for term babies was 40 +1 (37 +0, 43 +4 ) and 39 +5 (37 +0, 42 +6 ) for SOL and NSOL respectively. LMPT infants whose mothers had NSOL were more likely to receive resuscitation (21.7% v 14.5%; P = 0.005), respiratory support (16.2% v 8.6%; P = 0.001), intravenous fluids (34% v 21.5%; P = 0.005) and parenteral nutrition (6.0% v 1.7%; P = 0.001). In term-born infants, there were no differences in these outcomes between NSOL and SOL groups. Conclusion: Delivery following obstetric intervention is commoner at LMPT than term gestation. Effects associated with medically indicated LMPT delivery compound effects caused by prematurity. Further exploration of delivery indications may identify particularly high-risk groups.